2009
DOI: 10.1007/s00027-009-0110-6
|View full text |Cite
|
Sign up to set email alerts
|

Immune deficiency causes annual late summer brown trout (Salmo trutta) mortality in Austrian prealpine river systems

Abstract: For several years, severe brown trout (Salmo trutta) mortality has been observed in different prealpine river systems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The total number of blood cells was counted using a Bürker Türk counting chamber as described previously (Lahnsteiner et al., 2009) from ten different fields of the counting chamber. Thereafter the samples were stained in Giemsa stain for 30 min and the number of erythrocytes with normal appearance, aged or damaged erythrocytes having an irregular shape, an eccentric nucleus, or two nuclei, erythroblasts, fusiform and rounded thromboyctes, lymphocytes, and granulocytes were counted (Lahnsteiner et al., 2009).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The total number of blood cells was counted using a Bürker Türk counting chamber as described previously (Lahnsteiner et al., 2009) from ten different fields of the counting chamber. Thereafter the samples were stained in Giemsa stain for 30 min and the number of erythrocytes with normal appearance, aged or damaged erythrocytes having an irregular shape, an eccentric nucleus, or two nuclei, erythroblasts, fusiform and rounded thromboyctes, lymphocytes, and granulocytes were counted (Lahnsteiner et al., 2009).…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon is therefore called the ‘Schwarze Bachforelle Phänomen’ or ‘proliferative darkening syndrome’ (Born and Schwaiger, 2003). A recently published study (Lahnsteiner et al., 2009) showed that the affected fish suffered from severe immune deficiency because the number of peripheral blood granulocytes and lymphocytes, plasma lysozyme activity and plasma immunoglobulin levels were drastically reduced. Changes in the hematopoietic tissue of spleen and kidney were also observed (Lahnsteiner et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For decades, PDS has caused a massive decline of brown trout populations in the grayling zone of several pre-alpine rivers in Southern Germany [6,7]. These mass mortalities affect a major part of the brown trout population every late summer until autumn, whereas rainbow trout (Oncorhynchus mykiss) populations are not affected.…”
Section: Introductionmentioning
confidence: 99%